2021
DOI: 10.26740/jekobi.v4n1.p99-109
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Ekonomi Syariah terhadap Minat Mahasiswa Menabung di Bank Syariah

Abstract: The purpose of this research was to understand whether or not Islamic economics literacy influence college students saving interest in Islamic bank. The sampling technique used in purposive sampling technique with a population of study is college student of sharia economics, sharia banking, Islamic economics and sharia accounting major or study program in East Java which is calculated using the convenience formula. The study used a quantitative research method with questionnaire as the primary data. In testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Pada umumnya penelitianpenelitian yang telah ada menguji literasi keuangan syariah, pendidikan, dan pengetahuan tentang riba terhadap keputusan dan minat menabung atau melakukan pinjaman pada lembaga keuangan syariah dan konvensional. Penelitian yang dilakukan oleh (Ariyaningsih dkk., 2021;Nurudin dkk., 2021) pemahaman tentang riba mempengaruhi keputusan nasabah nasabah memilih bank syariah, penelitian (Firdiana & Fikriyah, 2021) menemukan literasi ekonomi syariah berpengaruh terhadap minat menabung, penelitian (Ghani & Saputra, 2016) menyatakan pendidikan berpengaruh signifikan terhadap pengetahuan masyarakat tentang bank syariah. Penelitian (Munthasar dkk., 2021) menemukan pengetahuan dan pendidikan berpengaruh terhadap literasi keuangan di masyarakat Aceh.…”
Section: Pendahuluanunclassified
“…Pada umumnya penelitianpenelitian yang telah ada menguji literasi keuangan syariah, pendidikan, dan pengetahuan tentang riba terhadap keputusan dan minat menabung atau melakukan pinjaman pada lembaga keuangan syariah dan konvensional. Penelitian yang dilakukan oleh (Ariyaningsih dkk., 2021;Nurudin dkk., 2021) pemahaman tentang riba mempengaruhi keputusan nasabah nasabah memilih bank syariah, penelitian (Firdiana & Fikriyah, 2021) menemukan literasi ekonomi syariah berpengaruh terhadap minat menabung, penelitian (Ghani & Saputra, 2016) menyatakan pendidikan berpengaruh signifikan terhadap pengetahuan masyarakat tentang bank syariah. Penelitian (Munthasar dkk., 2021) menemukan pengetahuan dan pendidikan berpengaruh terhadap literasi keuangan di masyarakat Aceh.…”
Section: Pendahuluanunclassified
“…Students attending Islamic universities often exhibit stronger religious convictions, leading to more positive views of Islamic banks as institutions in harmony with their faith, thereby fostering trust and a sense of moral responsibility in financial transactions (Janah et al, 2020;Mamuaya, 2018;Muslichah & Sanusi, 2019). Furthermore, a deeper understanding of the concept of Islamic finance plays a crucial role in shaping positive attitudes and interest in Islamic banking (Az-Zahra et al, 2022; Firdiana & Fikriyah, 2021). Research has shown that individuals who view their faith as an integral part of their identity are more inclined to opt for Islamic banking products and services (Mardiana et al, 2021;Sujianto et al, 2023).…”
Section: Jed | 38mentioning
confidence: 99%
“…Within Indonesia, Islamic universities play a pivotal role in shaping students' perceptions of Islamic banking (Firdiana & Fikriyah, 2021;Iryani & Kristanto, 2022). However, it is crucial to recognize that students' attitudes toward Islamic banks can exhibit substantial variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negara Indonesia menduduki urutan pertama di dunia yang memiliki jumlah warga negara muslim terbanyak. Sebagai wilayah yang mempunyai penduduk sebagian muslim, dapat mewujudkan industri yang berbasis syariah, salah satunya yaitu bank syariah (Firdiana and Fikriyah, 2021). Pengetahuan mahasiswa tentang bank syariah sangat mempengaruhi sikap mahasiswa terhadap produk yang akan ditawarkan, sehingga semakin baik pengetahuan mahasiswa mengenai bank syariah maka akan memacu minat mahasiswa untuk menjadi nasabah bank syariah (Maulina, 2021).…”
Section: Pendahuluanunclassified